A Matter of Scale: Developing a Framework for Environmental Archaeology in Brussels - Yannick Devos; Bea De Cupere; Lien Speleers; Katrien Van de Vijver; Nina Van Schepdael; Luc Vrydaghs; Ann Degraeve (Internet Archaeology)
Whereas environmental studies are today an important part of urban archaeological research in many towns and cities in Europe, they often focus on individual sites and do not always result in larger syntheses. To exploit the full potential of urban environmental studies in Brussels, Belgium, a specific framework has been developed, explicitly aimed at coping with the inherent complexity of urban investigations, including the variety of research themes that need to be dealt with, the challenges of fast-evolving environmental research, and how to address the needs of different stakeholders. This article discusses how the framework was created, the challenges that have been dealt with over the past few decades, and how we can further improve the framework for the future.